Video-Urodynamic Characteristics in Women with Urgency due to Detrusor Sphincter Dyssynergia and Idiopathic External Urethral Sphincter Hyperactivity (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: detrusor sphincter dyssynergia; sphincter hyperactivitiy; urgency; video-urodynamic